2008
DOI: 10.1002/jccs.200800041
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Voltammetric Determination of Lead and Tin by Adsorptive Differential Pulse Stripping Method and Orthogonal Signal Correction‐Partial Least Squares in Water Samples

Abstract: An adsorptive differential pulse stripping method for the simultaneous determination of lead and tin is proposed. The procedure involves an adsorptive accumulation of lead and tin on a hanging mercury drop electrode (HMDE), followed by oxidation of adsorbed lead and tin by voltammetric scan using differential pulse modulation. The optimum experimental conditions are: 0.2 mol L−1 HNO3, accumulation potential of −900 mV versus Ag/AgCl, accumulation time of 200 s, scan rate of 20 mV s−1 and pulse height of 80 mV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Paola 37 showed that multivariate linear regression coupled with successive projections algorithm (SPA-MLR) was an effective tool to provide qualitative interpretations as well as quantitative predictions for the voltammetric determination of heavy metals under complex conditions. Ali Niazi et al 38,39 compared partial least squares (PLS), orthogonal signal correction-partial least squares (OSC-PLS) and least-squares support vector machines (LS-SVM) to obtain the signals of lead and tin resolved at the HDME and thus determined them simultaneously. There are, however, few papers concerning the research on the resolution problem of these metals at the BiFE combined with chemometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…Paola 37 showed that multivariate linear regression coupled with successive projections algorithm (SPA-MLR) was an effective tool to provide qualitative interpretations as well as quantitative predictions for the voltammetric determination of heavy metals under complex conditions. Ali Niazi et al 38,39 compared partial least squares (PLS), orthogonal signal correction-partial least squares (OSC-PLS) and least-squares support vector machines (LS-SVM) to obtain the signals of lead and tin resolved at the HDME and thus determined them simultaneously. There are, however, few papers concerning the research on the resolution problem of these metals at the BiFE combined with chemometric methods.…”
Section: Introductionmentioning
confidence: 99%